A Semiotic of "natural" reading and contemplation (Encuentros, 2022)
Review of the work Semiotics: the experience of meaning through art and Literature published by Professor Manuel González de Ávila of University of Salamanca.
Keywords: Semiotics; Visualstudies; iconologies; literary criticism; transposition